ANALISIS PENGGUNAAN PASIR LAUT PADA CAMPURAN BETON TERHADAP RUMAH TAHAN GEMPA - Muhammad Fauzi (Inersia: Jurnal Teknik Sipil, 2019)
Bengkulu is an earthquake prone area, so that the construction of buildings/houses should be based on the concepts of earthquake resistant houses. But to make earthquake-resistant housing, people has been frequently use material sea sand as a mixture of concrete. Research on the use of sea sandas fine aggregate in concrete mix is background by the availability of sea sand in a very large number in the city of Bengkulu. This study aims to find out how big the compressive strength of concrete is produced when using sea sand with some treatments. The treatment used to the sea sand is without treatment, soaked for 24 hours and the addition of lime 5%, 10%, 15% by weight ofcement. Concrete planned to use fas 0.5 with a cylindrical sample and amount 30 pieces. The results showed that the use of sea sand in concrete mix was a mixture of concrete without treatment produces an average compressive strength of 16.65 MPa, the concrete mix with soaked treatment of 19.79 MPa, and the addition of lime 5%, 10%, 15% in the amount of 20,72 MPa, 20,72 MPa,18,69 MPa